Impacts of transboundary air pollution and local emissions on PM2.5 pollution in the Pearl River Delta region of China and the public health, and the policy implications - X Hou; C K Chan; G H Dong; S H L Yim (Environmental Research Letters, 2019)
Despite a downward trend in pollutant levels because of a series of emission control policies, the Pearl River Delta (PRD) region continues to suffer from a high number of fine particulate matter (PM _2.5 ) events and the resultant public health impacts. To effectively control PM _2.5 in the region, a comprehensive understanding of source contribution and PM _2.5 responses to various emission species is critical. We applied the Community Multiscale Air Quality Modeling System together with the high-order decoupled direct method, to simulate air quality and PM _2.5 sensitivity and examined PM _2.5 responses to emission species in the PRD region in the four seasons of 2010. We employed a concentration-response function to quantify the resultant number of premature mortalities attributable to outdoor PM _2.5 . We estimated that local and transboundary air pollution (TAP) contributed 27% and 73%, respectively, of the region’s PM _2.5 . In absolute terms, the largest impacts from local and TAP occurred in winter. With respect to relative contributions among the different sources, regional TAP (between cities in the region) (R-TAP) and local contributions had the largest effect in summer, whereas superregional TAP (from outside of the region) contributed the most in fall and winter. Outdoor PM _2.5 pollution caused 20 160 (95% confidence interval: 5100–39 310) premature mortalities every year in the PRD region. Averaging among cities, 50%, 20%, and 30% of these deaths were attributable to S-TAP, R-TAP, and local contributions, respectively. Precursor gas emissions (i.e. NH _3 , volatile organic compounds, SO _2 , and NO _x ) affect PM _2.5 level in a nonlinear manner; thus, individual pollutant control strategies are less effective for improving PM _2.5 pollution than an integrated strategy. On the basis of our findings, we recommend that controls for multiple emission species should be implemented to control PM _2.5 pollution in the region.